PEMBERDAYAAN KELOMPOK WANITA TANI MELALUI PEMBUATAN KERIPIK SAYURAN METODE VACUUM FRYING - Chotimah, Hastin Ernawati; Kusumadati, Wijantri; Taufik, Eka Nor (Universitas Tanjungpura, 2019)
Petuk Katimpun is one of the supplier villages for vegetable needs in the Palangka Raya city and its surroundings. At the abundant harvest, the prices of vegetables dropped sharply and were even worthless. Vegetables are left to rot in the tree, because there are costs to be taken to pick the vegetables. This is certainly very painful for the farmer. The farmers continue to lose money. One solution is to increase the value added of vegetables through processing technology. The technology of processing vegetable chips with vacuum frying is able to maintain the distinctive aroma and color of vegetables, crisper texture, lower vitamin damage and lower oil absorption. The purpose of this community service program is to transfer vacuum frying technology to increase the value added of the vegetables so that the level of the loss of farmers can be reduced. The approach were taken byÂ counseling, training and coaching and mentoring. The counseling was carried out by direct communication and interactive discussion, while training of using vacuum frying tools with various vegetable raw materials was carried out under the guidance of the service team. The coaching and group assistance were carried out in the acquisition of SPP-IRT as well as ways to access markets both directly and indirectly. The results of the community service program showed that 70% of partners were able to operate vacuum frying equipment. The capabilities of labeling and packaging were 100 % . They also had an ability to access markets indirectly through online media. The direct market could not be accessed due to Â the SPP-IRT certificate has not been obtained.Â Key words : community empowerment, vegetables chip, vacuum frying